Iron-based Fischer-Tropsch synthesis catalyst with low CO2 yield as well as preparation method and application thereof

By using pure silicon molecular sieve as a support, iron-based Fischer-Tropsch synthesis catalysts are prepared by impregnating metal Fe, Mg, and K precursors, solving the problem of high CO2 yield in existing catalysts, achieving high Fischer-Tropsch activity and low water vapor transformation reaction activity, improving energy and economic benefits, and in line with the "dual carbon" goal.

CN119746915APending Publication Date: 2025-04-04CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411744240.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing iron-based Fischer Tropsch synthesis catalysts have many catalytic by-products during Fischer Tropsch synthesis, especially the high yield of CO2, which leads to low energy and economic benefits and is contrary to the "dual carbon" goal.

Method used

A pure silicon molecular sieve was used as a support to immerse the precursors of metals Fe, Mg, and K to prepare an iron-based Fischer-Tropsch synthesis catalyst with low CO2 yield. The process includes preparing a catalyst precursor and obtaining a catalyst with low CO2 yield by calcination.

Benefits of technology

It significantly improves the performance of iron-based Fischer Tropsch synthesis catalyst, especially in reducing CO2 yield, improves the yield and selectivity of synthetic oil, reduces CO2 emissions, and conforms to the development trend of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746915A_ABST
    Figure CN119746915A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based Fischer-Tropsch synthesis catalyst with low CO2 yield as well as a preparation method and application of the iron-based Fischer-Tropsch synthesis catalyst. The preparation method comprises the following steps: 1) preparing a pure silicon molecular sieve carrier; 2) dissolving precursors of metals Fe, Mg and K in water, impregnating the pure silicon molecular sieve carrier according to 20-40% of metal iron loading capacity, and performing ultrasonic treatment, aging and drying on the obtained mixed solution to obtain a catalyst precursor; and 3) roasting the catalyst precursor to obtain the iron-based Fischer-Tropsch synthesis catalyst with low CO2 yield. The catalyst provided by the invention takes the pure silicon series molecular sieve as a carrier, and the weak interaction of the pure silicon molecular sieve and metal promotes the content of iron carbide phase in the activated catalyst, so that the conversion rate of raw materials is improved, and the yield of a byproduct CO2 is effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst, a preparation method and application thereof. Background Art

[0002] With the rapid development of the economy, energy problems are becoming increasingly serious. As an important energy resource, oil is facing the problem of depletion, forcing humans to develop new resources to replace oil. Compared with oil, coal resources on the earth are much more abundant. However, the current utilization of coal is mainly based on direct combustion, which brings a series of environmental problems that cannot be effectively solved. Using carbon-containing resources such as coal, oil and biomass as raw materials to produce synthesis gas, and then through Fischer-Tropsch Synthesis (FTS) to highly selectively and directional produce low-carbon olefins, oxygen-containing compounds and other chemicals is one of the research hotspots in recent years.

[0003] The conversion efficiency and product yield of Fischer-Tropsch synthesis are closely related to the performance of the catalyst. A large number of research results show that the metals with Fischer-Tropsch synthesis activity are mainly Group VIII transition metal elements. Compared with other metal elements, Fe is cheap, has extensive reserves, and has higher activity and higher olefin yield. Due to the complex phase changes of iron-based catalysts during reduction and Fischer-Tropsch reaction, it is particularly difficult to correlate the iron phase with the active phase of the Fischer-Tropsch reaction. With the deepening of research on iron-based Fischer-Tropsch synthesis catalysts, more and more researchers believe that iron carbide (FeC x ) is the active phase of the Fischer-Tropsch synthesis reaction, while Fe3O4 is the active center of the water gas shift (WGS).

[0004] However, due to the presence of water in the Fischer-Tropsch synthesis product, a water gas shift reaction occurs, which in turn greatly reduces the utilization rate of CO. The iron carbide formed during the reduction and carbonization process will be oxidized to Fe3O4 by the H2O generated in the reaction, which will cause its activity to change, further promoting the side reaction WGS reaction, and greatly reducing the catalytic performance. During the Fischer-Tropsch synthesis process, about 50% of CO is converted into C1 by-products such as CO2 (about 40%) and CH4. The utilization efficiency of carbon atoms is low, which seriously reduces the energy and economic benefits. Generally speaking, about 35% of CO is converted to CO2 through the water gas shift reaction on an iron catalyst, which leads to a significant increase in subsequent energy consumption and is contrary to the current "dual carbon" goal concept.

[0005] Therefore, the preparation of iron-based Fischer-Tropsch synthesis catalysts with improved performance is an urgent problem to be solved. Summary of the invention

[0006] The present invention aims to provide a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst, a preparation method and application thereof, so as to solve the technical problem of the iron-based Fischer-Tropsch synthesis catalyst having many catalytic by-products in the prior art.

[0007] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing an iron-based Fischer-Tropsch synthesis catalyst with a low CO2 yield is provided. The preparation method comprises: 1) preparing a pure silicon molecular sieve carrier; 2) dissolving precursors of metal Fe, Mg, and K in water, impregnating the pure silicon molecular sieve carrier with a metal iron loading of 20% to 40%, ultrasonically treating the obtained mixed solution, aging, and drying to obtain a catalyst precursor; 3) calcining the catalyst precursor to obtain an iron-based Fischer-Tropsch synthesis catalyst with a low CO2 yield.

[0008] Furthermore, the pure silicon molecular sieve carrier includes one or more selected from the group consisting of Beta molecular sieve after dealuminization by acid treatment and pure silicon Beta molecular sieve synthesized by hydrothermal synthesis, MCM-41 molecular sieve, SBA-15 molecular sieve, KIT-6 molecular sieve, and Silicalite-1 molecular sieve.

[0009] Furthermore, the reaction conditions of the acid-treatment dealumination include: a temperature of 80 to 120° C., a nitric acid concentration of 5 wt % to 65 wt %, and a stirring time of 12 h to 48 h.

[0010] Furthermore, in step 2), the precursor of metal Fe is selected from one or more of ferric nitrate nonahydrate, anhydrous ferric chloride, and ferric citrate; the precursor of metal Mg is selected from one or more of anhydrous magnesium chloride, magnesium sulfate, and magnesium oxide; the precursor of metal K is selected from one or more of potassium chloride, potassium carbonate, and potassium nitrate.

[0011] Furthermore, in step 2), the contents of metal Mg and K in the precursor solution are doped according to the element molar ratio of Mg / Fe=0.05-0.5 and K / Fe=0.05-0.2.

[0012] Furthermore, the drying temperature in step 2) is 80-120°C; and / or the calcining temperature in step 3) is 450-600°C.

[0013] Furthermore, the calcination temperature in step 3) is 550°C.

[0014] Furthermore, in step 3), the calcination conditions are 450-600° C. for 3-5 hours, and the heating rate is 2° C. / min-10° C. / min.

[0015] According to another aspect of the present invention, a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst is provided. The low CO2 yield iron-based Fischer-Tropsch synthesis catalyst is prepared by any of the above-mentioned methods for preparing a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst.

[0016] According to another aspect of the present invention, a Fischer-Tropsch synthesis method is provided, which comprises contacting a mixture of carbon monoxide and hydrogen with a catalyst under Fischer-Tropsch synthesis reaction conditions, wherein the catalyst is the low CO2 yield iron-based Fischer-Tropsch synthesis catalyst of the present application.

[0017] The catalyst of the present application uses pure silicon series molecular sieves as carriers, and is divided into one-dimensional structure: MCM-41 molecular sieve; two-dimensional structure: SBA-15 molecular sieve; three-dimensional pore structure: KIT-6, Silicalite-1, pure silicon Beta molecular sieve, and the active component is iron. On this basis, the supported iron-based catalyst is regulated by K and Mg additives to further strengthen the regulation of the Fischer-Tropsch synthesis reaction products. The weak interaction between pure silicon molecular sieves and metals promotes the content of iron carbide phase in the catalyst after activation, thereby improving the conversion rate of the raw material and effectively suppressing the byproduct CO2 yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 A schematic diagram showing the results of X-ray diffraction (XRD) tests on catalysts A1 to A13 and B1 to B5 is shown;

[0020] Figure 2 The N2 desorption curve and pore size distribution diagram of different pure silicon molecular sieves as supported catalysts are shown;

[0021] Figure 3 A schematic diagram showing the reaction results of CO conversion rate and CO2 selectivity of each catalyst over time;

[0022] Figure 4 The CO conversion and CO2 selectivity of different catalysts are shown;

[0023] Figure 5 shows the H2-TPR spectra of catalysts A1 and A2; and

[0024] Figure 6 H2-TPR spectra of catalysts A2-A6 are shown. DETAILED DESCRIPTION

[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0026] In view of the technical problem that the iron-based Fischer-Tropsch synthesis catalyst in the prior art produces many catalytic byproducts, the present application provides a method for preparing an iron-based Fischer-Tropsch synthesis catalyst with a low CO2 yield. The preparation method is simple, and the obtained catalyst has high activity and low CO2 yield. In the present application, by selecting a suitable pure silicon molecular sieve for application in an iron-based Fischer-Tropsch synthesis catalyst, the reduction and carburization on the catalyst surface during the Fischer-Tropsch synthesis reaction are promoted, thereby increasing the iron carbide phase content in the catalyst to suppress the high-activity WGSR side reaction, that is, the problem of causing a high byproduct CO2.

[0027] According to a typical embodiment of the present application, a method for preparing an iron-based Fischer-Tropsch synthesis catalyst with a low CO2 yield is provided. The preparation method comprises: 1) preparing a pure silicon molecular sieve carrier; 2) dissolving precursors of metal Fe, Mg, and K in water, and impregnating the pure silicon molecular sieve carrier with a metal iron loading of 20% to 40% (i.e., the mass content of the Fe element in the catalyst after loading, i.e., Fe / (Fe+carrier), 20 to 40%), ultrasonically treating the obtained mixed solution, aging, and drying to obtain a catalyst precursor; 3) calcining the catalyst precursor to obtain an iron-based Fischer-Tropsch synthesis catalyst with a low CO2 yield.

[0028] In this application, pure silicon molecular sieve is selected as the carrier. While loading a high content of Fe as much as possible, it can also improve the reduction and carbonization of the catalyst and ensure the stability of the active phase of the Fischer-Tropsch reaction in the catalyst. This can not only improve the conversion rate of synthesis gas and the utilization rate of raw materials, but also inhibit the water vapor shift reaction and reduce the yield of CO2 in the product, so as to achieve high Fischer-Tropsch activity and low water vapor shift reaction activity of the catalyst. The reasonable loading amount of Fe can ensure that the catalyst has sufficient active sites, while avoiding the blockage of active centers caused by excessive loading, which is conducive to improving the activity and selectivity of the catalyst and is suitable for Fischer-Tropsch synthesis reactors of various sizes.

[0029] In the present application, Mg and K etc. are auxiliary components of conventional Fischer-Tropsch synthesis catalysts. Even without the addition of these auxiliary components, the Fischer-Tropsch reaction can have considerable activity or stability. However, the addition of these auxiliary components can improve the catalytic properties of the catalyst.

[0030] In the present application, the pure silicon molecular sieve carrier that can be used includes but is not limited to one or more of the Beta molecular sieve selected from the acid-treated dealumination and hydrothermal synthesis (e.g., hydrothermal crystallization synthesis method), MCM-41 molecular sieve, SBA-15 molecular sieve, KIT-6 molecular sieve, and Silicalite-1 molecular sieve. The weak interaction between the pure silicon molecular sieve and the metal promotes the content of the iron carbide phase in the catalyst after activation, thereby improving the conversion rate of the raw material and effectively suppressing the byproduct CO2 yield; and these pure silicon molecular sieves can provide a good diffusion path, which is conducive to the rapid transmission of reactants and products, improves the reaction efficiency, and is particularly suitable for the Fischer-Tropsch synthesis reaction that requires a high diffusion rate; and the pore structure of the molecular sieve can provide a large surface area, enhance the interaction between the metal and the carrier, and improve the activity and stability of the catalyst, which is particularly suitable for the Fischer-Tropsch synthesis reaction that requires a high surface area and stability catalyst.

[0031] According to a typical embodiment of the present application, the reaction conditions of dealumination by acid treatment include: a temperature of 80 to 120°C, more preferably 100°C, a nitric acid concentration of 5wt% to 65wt%, more preferably 65wt%, and a stirring time of 12h to 48h, more preferably 24h. In the present application, the temperature adjustment during the acid treatment process can be selected according to the prior art, such as jacket heating, electric heating, etc., and the pH value adjustment during the acid treatment process can also be selected according to the prior art, such as by adjusting the mass fraction of the nitric acid solution. After the acid treatment is completed, the system is cooled for a period of time, and the precipitate is separated by means of suction filtration or centrifugation. Preferably, the obtained mixture is obtained by centrifugation and washing with deionized water to reduce solid loss and improve the yield of the product.

[0032] In one embodiment of the present application, in step 2), the metal Fe precursor is selected from one or more of ferric nitrate nonahydrate, anhydrous ferric chloride, and ferric citrate; the metal Mg precursor is selected from one or more of anhydrous magnesium chloride, magnesium sulfate, and magnesium oxide; the metal K precursor is selected from one or more of potassium chloride, potassium carbonate, and potassium nitrate. Preferably, it is a combination of ferric nitrate nonahydrate, anhydrous magnesium chloride, and potassium carbonate. In the present application, the metal additive Mg may be in the form of ferromagnesian crystal stone, the characteristic peak of the K additive is not obvious, and Fe is in the form of Fe2O3. This can be determined by X-ray diffraction (XRD) testing. By using these metal precursors, the metal distribution and morphology of the catalyst can be optimized, the reducibility and anti-poisoning ability of the catalyst can be enhanced, and a more efficient and stable catalytic performance can be achieved in Fischer-Tropsch synthesis.

[0033] According to a typical implementation of the present application, in step 2), the metallic iron loading in the precursor solution is 20% to 40%, and the contents of metallic Mg and K are doped according to Mg / Fe=0.05 to 0.5 (element molar ratio), K / Fe=0.05 to 0.2. Preferably, the metallic iron loading is 30% to 35%. Too little Fe content is insufficient to provide sufficient active centers for Fischer-Tropsch synthesis, while too much Fe content will lead to clustering of active centers, affecting the dispersion effect of the particles, resulting in a reduction in the contact area with the raw materials and a decrease in its activity.

[0034] Preferably, Mg / Fe=0.2 (element molar ratio). The introduction of Mg additive can increase the alkaline sites on the surface of the active phase, further adsorb CO2, increase the concentration of CO2 near the active sites, and further promote the reverse movement of WGSR to reduce the yield of byproduct CO2. And as the content of Mg additive increases, the CO2 yield is lower, but more additives will cover certain active sites, resulting in a decrease in the conversion rate of the catalyst. That is, by precisely controlling the doping ratio of Mg and K, the electronic structure of the catalyst can be optimized, its selectivity can be improved, and the generation of byproducts can be reduced.

[0035] Preferably, K / Fe=0.2 (element molar ratio). The abundant basic sites that K can effectively provide contribute to the high CO / H2 ratio on the catalyst surface, promote the CC chain growth reaction, and benefit olefins and C5 + The formation of products, at the same time, the K additive can further improve the reaction activity, but the CO2 yield in the product is also greatly improved.

[0036] According to a typical embodiment of the present application, the drying temperature in step 2) is 80-120°C; and / or the calcination temperature in step 3) is 450-600°C, preferably 550°C. Preferably, in step 3), the calcination conditions are calcination at 450-600°C for 3-5h, and the heating rate is 2°C / min-10°C / min. Controlling the heating rate can effectively avoid the destruction of the catalyst structure, ensure that the catalyst still maintains a good pore structure and metal dispersion at high temperature, which is beneficial to improve the service life of the catalyst and reduce production costs, and is suitable for continuous operation of the Fischer-Tropsch synthesis device. Calcination in air can ensure the formation of an oxide layer on the surface of the catalyst, which is beneficial to improve the heat resistance and wear resistance of the catalyst, and is particularly suitable for Fischer-Tropsch synthesis reactors that require long-term stable operation. The calcination condition is a temperature range of 450-600°C, which can ensure that the metal precursor of the catalyst is fully converted into an active metal species, while avoiding the destruction of the carrier structure, which is beneficial to improve the activity and stability of the catalyst, and is suitable for various types of Fischer-Tropsch synthesis reactions. Controlling the calcination time for 3 to 5 hours can ensure that the metal species of the catalyst are fully activated, while avoiding the loss of activity caused by over-calcination, which is beneficial to improving the performance of the catalyst and reducing energy consumption, and is suitable for high-efficiency Fischer-Tropsch synthesis reaction devices.

[0037] According to a typical embodiment of the present application, a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst is provided. The low CO2 yield iron-based Fischer-Tropsch synthesis catalyst is prepared by any of the above-mentioned methods for preparing the low CO2 yield iron-based Fischer-Tropsch synthesis catalyst.

[0038] The preparation method of the present application significantly improves the performance of the iron-based Fischer-Tropsch synthesis catalyst by precisely controlling the elemental molar ratio of Fe, Mg and K and specific roasting conditions, especially in reducing the CO2 yield. The use of this catalyst can not only effectively improve the yield and selectivity of synthetic oil, but also reduce the emission of CO2, which is environmentally friendly and in line with the development trend of green chemistry. In addition, the preparation process of the catalyst is simple, the cost is low, and it is easy to industrialize, which provides new possibilities for the optimization and upgrading of the Fischer-Tropsch synthesis process and has significant economic and environmental benefits.

[0039] According to a typical embodiment of the present application, a Fischer-Tropsch synthesis method is provided. The Fischer-Tropsch synthesis method comprises contacting a mixture of carbon monoxide and hydrogen with a catalyst under Fischer-Tropsch synthesis reaction conditions, wherein the catalyst is a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst of the present application.

[0040] The beneficial effects of the present application will be further described below with reference to embodiments.

[0041] Example 1

[0042] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a commercial Beta molecular sieve, and the iron loading in the catalyst is 40%. The preparation method is as follows:

[0043] (1) The precursor solution of metallic iron was loaded into commercial Beta molecular sieves by an equal volume impregnation method at a metal loading of 40%. 1.0 g of commercial Beta molecular sieves (Si / Al=25) was weighed, and 4.81 g of Fe(NO3)3·9H2O was weighed and dissolved in 2 ml of deionized water;

[0044] (2) The prepared precursor solution is loaded on the commercial Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added dropwise onto the commercial Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is sonicated for 1 hour, aged at room temperature overnight, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground;

[0045] (3) The obtained catalyst powder was calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into tablets with a mesh size of 20 to 40 to finally obtain Catalyst A1.

[0046] Example 2

[0047] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a pure silicon Beta molecular sieve prepared after acid treatment, and the iron loading in the catalyst is 40%. The preparation method is as follows:

[0048] (1) Pure silicon Beta molecular sieve was prepared by acid treatment. 275 ml of 65% wt% concentrated nitric acid was weighed and added into a three-necked flask. 15 g of commercial Beta molecular sieve (Si / Al=25) was added at the same time. Then, the mixture was stirred in an oil bath at 100° C. for 24 h. The obtained mixture was cooled, centrifuged, washed with deionized water until pH=7, and the obtained solid was dried in an oven at 80° C. for 12 h to obtain pure silicon Beta molecular sieve (Si / Al>1300).

[0049] (2) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%. Weigh 1.0 g of pure silicon Beta molecular sieve, weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 1 ml of deionized water;

[0050] (3) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst A2.

[0051] Example 3

[0052] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is an MCM-41 molecular sieve prepared by a hydrothermal method, and the iron loading in the catalyst is 40%. The preparation method is as follows:

[0053] (1) Add NaOH solution to the aqueous solution of CTAB and stir for 15 minutes. Then, add TEOS drop by drop into the stirred mixed solution. After the titration is completed, stir for another 2 hours. The mixed solution is placed in a polytetrafluoroethylene-lined reactor and hydrothermally treated at 110°C for 48 hours. The molar ratio of the reactants is 0.12CTAB: 1TEOS: 0.24NaOH: 66.7H2O.

[0054] Finally, the mixture was washed with deionized water, filtered, and dried at 100° C. overnight to obtain a white powder, which was then calcined at 550° C. in an air atmosphere to remove the template, thereby obtaining the MCM-41 molecular sieve white powder.

[0055] (2) The precursor solution of metallic iron was loaded into the MCM-41 molecular sieve by an equal volume impregnation method according to a metal loading of 40%. Weigh 1.0 g of MCM-41 molecular sieve (one-dimensional), weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 2.5 ml of deionized water;

[0056] (3) The prepared precursor solution was loaded into the MCM-41 molecular sieve by an equal volume impregnation method. The specific steps were as follows: the precursor solution was added dropwise onto the MCM-41 molecular sieve carrier with a rubber-tipped dropper and mixed evenly. The resulting mixed solution was ultrasonicated for 1 h, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying. The resulting catalyst powder was calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into tablets with a size of 20 to 40 mesh to finally obtain catalyst A3.

[0057] Example 4

[0058] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is an SBA-15 molecular sieve prepared by a hydrothermal method, and the iron loading in the catalyst is 40%. The preparation method is as follows:

[0059] (1) Weigh 2.0 g of P123 into a beaker, add 75 g of 1.6 M hydrochloric acid solution, stir in a 40° C. water bath for 4.5 h until P123 is completely dissolved and the solution changes color to light blue, then add 4.25 g of TEOS dropwise, continue stirring and ageing for 24 h, pour the resulting milky white solution into a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, crystallize at 100° C. for 24 h, wash with deionized water, filter, and dry at 100° C. overnight to obtain a white powder, which is then calcined at 550° C. in an air atmosphere to remove the template P123, thereby obtaining a white powder of SBA-15 molecular sieve.

[0060] (2) The precursor solution of metallic iron was loaded into the SBA-15 molecular sieve by an equal volume impregnation method according to a metal loading of 40%. Weigh 1.0 g of SBA-15 molecular sieve (two-dimensional), weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 3.5 ml of deionized water;

[0061] (3) The prepared precursor solution was loaded on the SBA-15 molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution was added dropwise onto the SBA-15 molecular sieve carrier with a rubber-tipped dropper and mixed evenly. The resulting mixed solution was ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying. The resulting catalyst powder was calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into tablets with a mesh size of 20 to 40 to finally obtain catalyst A4.

[0062] Example 5

[0063] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a KIT-6 molecular sieve prepared by a hydrothermal method, and the iron loading in the catalyst is 40%. The preparation method is as follows:

[0064] (1) Weigh 2.0 g of P123 in a beaker, add 3.933 g of 37% concentrated hydrochloric acid, and add 72.33 g of deionized water. Stir for 4.0 h in a 35°C water bath until P123 is completely dissolved and the solution changes color to light blue, then continue to add 2.0 g of n-butanol dropwise and continue stirring for 1 h, add 4.3 g of TEOS dropwise, continue stirring and aging at 35°C for 24 h, pour the resulting milky white solution into a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, crystallize at 100°C for 24 h, wash with deionized water, filter, and dry at 100°C overnight to obtain a white powder, which is then calcined at 550°C in an air atmosphere to remove the template P123, thereby obtaining a white powder of KIT-6 molecular sieve.

[0065] (2) The precursor solution of metallic iron was loaded into KIT-6 molecular sieve by equal volume impregnation method according to the metal loading amount of 40%. Weigh 1.0 g of KIT-6 molecular sieve (three-dimensional), weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 3.5 ml of deionized water;

[0066] (3) The obtained catalyst particles were calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into tablets with a mesh size of 20 to 40 to finally obtain Catalyst A5.

[0067] Example 6

[0068] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a Silicalite-1 molecular sieve prepared by a hydrothermal method, and the iron loading in the catalyst is 40%. The preparation method is as follows:

[0069] (1) Weigh 7.32 g of anhydrous ethanol into a beaker, add 7.74 g of tetrapropylammonium hydroxide, and add 42.9 g of deionized water. Stir at room temperature for 30 min, continue to add 8.26 g of TEOS dropwise, continue stirring and aging at room temperature for 6 h, pour the resulting transparent solution into a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, crystallize at 150°C for 48 h, wash with deionized water, filter, and dry at 100°C overnight to obtain a white powder, which is then calcined at 550°C in an air atmosphere to remove the template, thereby obtaining a white powder of Silicalite-1 molecular sieve.

[0070] (2) The precursor solution of metallic iron was loaded into the Silicalite-1 molecular sieve by an equal volume impregnation method according to a metal loading of 40%. 1.0 g of Silicalite-1 molecular sieve (three-dimensional) was weighed, 4.81 g of Fe(NO3)3·9H2O was weighed and dissolved in 3.0 ml of deionized water;

[0071] (3) The obtained catalyst particles were calcined in a muffle furnace in air at 550°C for 6 hours, and then pressed into tablets with a size of 20 to 40 meshes to finally obtain catalyst A6.

[0072] Example 7

[0073] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a commercial Beta molecular sieve, and the iron loading in the catalyst is 20%. The preparation method is as follows:

[0074] (1) The precursor solution of metallic iron was loaded into commercial Beta molecular sieves by an equal volume impregnation method at a metal loading of 20%. 1.0 g of commercial Beta molecular sieves (Si / Al=25) was weighed, and 2.40 g of Fe(NO3)3·9H2O was weighed and dissolved in 2 ml of deionized water;

[0075] (2) The prepared precursor solution is loaded on the commercial Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added dropwise onto the commercial Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is sonicated for 1 hour, aged at room temperature overnight, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground;

[0076] (3) The obtained catalyst powder was calcined in a muffle furnace in air at 550°C for 6 hours, and then pressed into tablets with a mesh size of 20 to 40 to finally obtain catalyst A7.

[0077] Example 8

[0078] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a commercial Beta molecular sieve, and the iron loading in the catalyst is 30%. The preparation method is as follows:

[0079] (1) The precursor solution of metallic iron was loaded into commercial Beta molecular sieves by an equal volume impregnation method at a metal loading of 30%. 1.0 g of commercial Beta molecular sieves (Si / Al=25) was weighed, and 3.61 g of Fe(NO3)3·9H2O was weighed and dissolved in 2 ml of deionized water;

[0080] (2) The prepared precursor solution is loaded on the commercial Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added dropwise onto the commercial Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is sonicated for 1 hour, aged at room temperature overnight, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground;

[0081] (3) The obtained catalyst powder was calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into tablets with a mesh size of 20 to 40 to finally obtain catalyst A8.

[0082] Example 9

[0083] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a pure silicon Beta molecular sieve prepared after acid treatment, the iron loading in the catalyst is 40%, and the acid treatment dealumination method is basically the same as that in Example 2, except that the treatment temperature is 80°C and the stirring time is 48h. The preparation method is as follows:

[0084] (1) Pure silicon Beta molecular sieve was prepared by acid treatment. 275 ml of 65% wt% concentrated nitric acid was weighed and added into a three-necked flask. 15 g of commercial Beta molecular sieve (Si / Al=25) was added at the same time. Then, the mixture was stirred in an oil bath at 80°C for 48 h. The obtained mixture was cooled, centrifuged, washed with deionized water until pH=7, and the obtained solid was dried in an oven at 80°C for 12 h to obtain pure silicon Beta molecular sieve (Si / Al>1000).

[0085] (2) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%. Weigh 1.0 g of pure silicon Beta molecular sieve, weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 1 ml of deionized water;

[0086] (3) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst A9.

[0087] Example 10

[0088] A method for preparing a Fe-based Fischer-Tropsch synthesis catalyst with a low CO2 yield, wherein the carrier used in the preparation method is a pure silicon Beta molecular sieve prepared after acid treatment, the iron loading in the catalyst is 40%, and the acid treatment dealumination method is basically the same as that in Example 2, except that the treatment temperature is 120°C and the stirring time is 12h. The preparation method is as follows:

[0089] (1) Pure silicon Beta molecular sieve was prepared by acid treatment. 275 ml of 65% wt% concentrated nitric acid was weighed and added into a three-necked flask. 15 g of commercial Beta molecular sieve (Si / Al=25) was added at the same time. Then, the mixture was stirred in an oil bath at 120° C. for 12 h. The obtained mixture was cooled, centrifuged, washed with deionized water until pH=7, and the obtained solid was dried in an oven at 80° C. for 12 h to obtain pure silicon Beta molecular sieve (Si / Al>1000).

[0090] (2) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%. Weigh 1.0 g of pure silicon Beta molecular sieve, weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 1 ml of deionized water;

[0091] (3) The prepared precursor solution is loaded on pure silicon Beta molecular sieve by equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop onto the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly. The resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying. The resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst A10.

[0092] Embodiment 11

[0093] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a pure silicon Beta molecular sieve prepared after acid treatment, the iron loading in the catalyst is 40%, and the acid treatment dealumination method is basically the same as that in Example 2, except that the nitric acid concentration is 30wt% and the stirring time is 36h. The preparation method is as follows:

[0094] (1) Pure silicon Beta molecular sieve was prepared by acid treatment. 275 ml of 65% wt% concentrated nitric acid was weighed and added to a three-necked flask. 15 g of commercial Beta molecular sieve (Si / Al=25) was added at the same time. Then, the mixture was stirred in an oil bath at 100° C. for 36 h. The obtained mixture was cooled, centrifuged, washed with deionized water until pH=7, and the obtained solid was dried in an oven at 80° C. for 12 h to obtain pure silicon Beta molecular sieve (Si / Al>1000).

[0095] (2) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%. Weigh 1.0 g of pure silicon Beta molecular sieve, weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 1 ml of deionized water;

[0096] (3) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop onto the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst A11.

[0097] Example 12

[0098] A method for preparing a Fe-based Fischer-Tropsch synthesis catalyst with low CO2 yield, wherein the carrier used in the preparation method is a high-silicon Beta molecular sieve prepared after acid treatment, the iron loading in the catalyst is 40%, and the acid treatment dealumination method is basically the same as that in Example 2, except that the nitric acid concentration is 5wt% and the stirring time is 36h. The preparation method is as follows:

[0099] (1) Prepare high-silicon Beta molecular sieve by acid treatment: weigh 275 ml of 65% wt% concentrated nitric acid and add it into a three-necked flask, and add 15 g of commercial Beta molecular sieve (Si / Al=25), then stir in an oil bath at 80°C for 24 hours; cool the resulting mixture, wash it with deionized water to pH=7 by centrifugation, and dry the resulting solid in an oven at 80°C for 12 hours to obtain high-silicon Beta molecular sieve (Si / Al>100);

[0100] (2) The precursor solution of metallic iron was loaded into the high-silicon Beta molecular sieve by an equal volume impregnation method according to a metal loading of 40%. Weigh 1.0 g of pure silicon Beta molecular sieve, weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 1 ml of deionized water;

[0101] (3) The prepared precursor solution is loaded in the high-silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst A12.

[0102] Example 13

[0103] A method for preparing a low CO2 yield Fe-based Fischer-Tropsch synthesis catalyst, wherein the carrier used in the preparation method is a pure silicon Beta molecular sieve prepared after acid treatment, the iron loading in the catalyst is 40%, and the acid treatment dealumination method is basically the same as that in Example 2, except that: in step 3, the calcination temperature is 450°C and the calcination time is 12 hours. The preparation method is as follows:

[0104] (1) Pure silicon Beta molecular sieve was prepared by acid treatment. 275 ml of 65% wt% concentrated nitric acid was weighed and added into a three-necked flask. 15 g of commercial Beta molecular sieve (Si / Al=25) was added at the same time. Then, the mixture was stirred in an oil bath at 100° C. for 24 h. The obtained mixture was cooled, centrifuged, washed with deionized water until pH=7, and the obtained solid was dried in an oven at 80° C. for 12 h to obtain pure silicon Beta molecular sieve (Si / Al>1300).

[0105] (2) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%. Weigh 1.0 g of pure silicon Beta molecular sieve, weigh 4.81 g of Fe(NO3)3·9H2O and dissolve them in 1 ml of deionized water;

[0106] (3) The prepared precursor solution is loaded in pure silicon Beta molecular sieve by equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the obtained mixed solution is ultrasonicated for 1 hour, aged at room temperature overnight, and then transferred to an oven at 100°C for complete drying, and the obtained catalyst is ground. The obtained catalyst powder is calcined in a muffle furnace at 450°C in air for 12 hours, and then pressed into 20-40 mesh to finally obtain catalyst A13.

[0107] Comparative Example 1

[0108] A catalyst comparison sample of Mg-doped Fe-supported pure silicon molecular sieve was prepared. The synthesis method is as follows:

[0109] (1) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%, and the Mg additive was doped according to Mg / Fe=0.2 (element molar ratio). Weigh 1.0g of pure silicon Beta molecular sieve, weigh 4.81g of Fe(NO3)3·9H2O and 0.2262g of anhydrous MgCl2 and dissolve them in 1ml of deionized water;

[0110] (2) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop onto the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into tablets with a mesh size of 20 to 40 to finally obtain catalyst B1.

[0111] Comparative Example 2

[0112] A catalyst comparison sample of Fe-supported pure silicon molecular sieve doped with K promoter was prepared. The synthesis method is as follows:

[0113] (1) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%, and K additive was doped according to K / Fe=0.2 (element molar ratio). 1.0g of pure silicon Beta molecular sieve, 4.81g of Fe(NO3)3·9H2O and 0.1644g of K2CO3 were weighed and dissolved in 1ml of deionized water;

[0114] (2) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst B2.

[0115] Comparative Example 3

[0116] A catalyst comparison sample of Fe-supported pure silicon molecular sieve doped with Mg and K additives was prepared. The synthesis method is as follows:

[0117] (1) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%, and Mg and K additives were doped according to Mg / Fe=0.2 (element molar ratio) and K / Fe=0.2 (element molar ratio). Weigh 1.0g of pure silicon Beta molecular sieve, weigh 4.81g of Fe(NO3)3·9H2O, 0.2262g of anhydrous MgCl2 and 0.1644g of K2CO3 and dissolve them in 1ml of deionized water;

[0118] (2) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst B3.

[0119] Comparative Example 4

[0120] A catalyst comparison sample of Fe-supported pure silicon molecular sieve doped with Mg and K additives was prepared. It was basically the same as Comparative Example 3, except that Mg / Fe=0.05 (element molar ratio) and K / Fe=0.05 (element molar ratio). The synthesis method is as follows:

[0121] (1) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%, and Mg and K additives were doped according to Mg / Fe=0.2 (element molar ratio) and K / Fe=0.2 (element molar ratio). Weigh 1.0g of pure silicon Beta molecular sieve, weigh 4.81g of Fe(NO3)3·9H2O, 0.0565g of anhydrous MgCl2 and 0.0411g of K2CO3 and dissolve them in 1ml of deionized water;

[0122] (2) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged overnight at room temperature, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into 20-40 mesh to finally obtain catalyst B4.

[0123] Comparative Example 5

[0124] A catalyst comparison sample of Fe-supported pure silicon molecular sieve doped with Mg and K additives was prepared. It was basically the same as Comparative Example 3, except that Mg / Fe=0.5 (element molar ratio) and K / Fe=0.05 (element molar ratio). The synthesis method was as follows:

[0125] (1) The precursor solution of metallic iron was loaded into pure silicon Beta molecular sieve by equal volume impregnation method according to the metal loading amount of 40%, and Mg and K additives were doped according to Mg / Fe=0.5 (element molar ratio) and K / Fe=0.05 (element molar ratio). Weigh 1.0g of pure silicon Beta molecular sieve, weigh 4.81g of Fe(NO3)3·9H2O, 0.5655g of anhydrous MgCl2 and 0.0411g of K2CO3 and dissolve them in 1ml of deionized water;

[0126] (2) The prepared precursor solution is loaded on the pure silicon Beta molecular sieve by an equal volume impregnation method. The specific steps are as follows: the precursor solution is added drop by drop to the pure silicon Beta molecular sieve carrier with a rubber-tipped dropper and mixed evenly, the resulting mixed solution is ultrasonicated for 1 hour, aged at room temperature overnight, and then transferred to an oven at 100°C for complete drying, and the resulting catalyst is ground. The resulting catalyst powder is calcined in a muffle furnace at 550°C in air for 6 hours, and then pressed into tablets with a mesh size of 20 to 40 to finally obtain catalyst B5.

[0127] The Fischer-Tropsch synthesis activity test was carried out on the Fischer-Tropsch catalysts (A1-A13, B1-B5) prepared in the examples and comparative examples.

[0128] X-ray diffraction (XRD) tests were performed on catalysts A1-A13 and B1-B5. The test results are as follows: Figure 1 As shown, by comparing with the standard card, the X-ray diffraction characteristic peaks of the catalyst sample are consistent with the standard PDF card 82-2359, indicating that the Fe exists in the form of Fe2O3.

[0129] Figure 2 The N2 desorption curves and pore size distribution diagrams of catalysts with different pure silicon molecular sieves as carriers. Different catalysts all show H1-type hysteresis loops, indicating the existence of mesoporous structures, which is also the main reason for the high catalytic activity of the catalysts.

[0130] Figure 3 The CO conversion rate and CO2 selectivity of each catalyst in Examples A1-A13 are the reaction results over time, Figure 4 The CO conversion rate and CO2 selectivity of different catalysts are corresponding to the data in Table 1.

[0131] Figure 5 , Figure 6 H2-TPR spectra of catalysts (A1-A6) with different molecular sieves as carriers. Figure 5 , Figure 6This indicates that there are differences in the interaction between the active center Fe and the carrier. Among them, the catalyst (A2) with pure silicon Beta molecular sieve as the carrier has the weakest interaction between the carrier and the metal, which makes Fe2O3 generate more iron carbide active centers during the reduction and carburization process, further inhibiting the occurrence of the water gas shift reaction.

[0132] The Fischer-Tropsch synthesis activity of the above catalysts A1-A13 and B1-B5 was evaluated using a laboratory fixed-bed microreactor. The catalyst loading was 1.0 g, and 6.0 g of quartz sand of the same size was used for dilution to ensure the constant temperature zone of the reaction temperature. The catalyst was first pre-reduced online in the reactor at 270°C under normal pressure for 24 hours with synthesis gas, and then the H2 / CO ratio and reaction pressure were gradually switched to the evaluation conditions to start the Fischer-Tropsch synthesis reaction. The evaluation conditions are: 250°C, 1.5MPa. The space velocity of the synthesis gas in the reactor is 40-80mL / g-cat / min, and the hydrogen-carbon ratio is 1.5-3.0. The data results are shown in Table 1. The reaction performance evaluation conditions of the catalyst in Table 1 are: H2 / CO=1.5-3.0, T=310°C, P=1.5MPa, SV=2500-6000mL / (h·g), t=460-480h. The reaction results are as follows:

[0133] Table 1 Catalytic performance test of different catalysts

[0134]

[0135] The data in Table 1 show that Catalyst A2 can significantly suppress the CO2 yield and has a CO conversion rate of more than 80%. This is because the pure silicon Beta molecular sieve has a weaker interaction with the active center, which promotes the reduction and carburization of the catalyst and produces more iron carbide. Therefore, it has a higher Fischer-Tropsch reaction activity and inhibits the occurrence of the water gas shift reaction to a certain extent.

[0136] Comparison of catalysts B1 and B2 doped with K and Mg additives shows that the doping with K additive reduces the yield of CH4, while the yield of CO2 is greatly improved; while the doping with Mg additive introduces alkaline sites, while adsorbing CO2, it inhibits the forward movement of the water gas shift reaction, resulting in a decrease in the yield of CO2. However, the addition of Mg additive leads to the appearance of ferromagnesian crystals, which inhibits the reduction of part of the iron oxide, resulting in a decrease in the activity of the catalyst.

[0137] The catalysts were tested for specific surface area and pore volume; the catalysts A1-A6 were analyzed by low temperature nitrogen adsorption method, and the analysis results are shown in Table 2. The BET specific surface area of ​​the catalysts of the present invention is 160-420 m 2 / g, pore size is 2.41~6.57nm, pore volume is 0.06~0.4cm 3 / g.

[0138] Table 2 Specific surface area and pore structure data of different catalysts

[0139]

[0140] As shown in Table 2, catalysts A2 and A5 have the largest pore sizes, which are 6.57 nm and 5.40 nm, respectively. Catalysts A2 and A6 have the smallest pore volumes, which are 0.12 and 0.06 cm, respectively. 3 / g, indicating that the active center Fe in the catalyst is more evenly dispersed, which is also the main reason for the high catalytic activity of the catalyst.

[0141] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the method for preparing a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst of the present application uses pure silicon molecular sieves of different structures as carriers and metal inorganic salts of Fe, Mg, and K as their metal precursors. The preparation process is simple, the CO conversion rate is high, and the effect of inhibiting the by-product CO2 is obvious.

[0142] Compared with conventional carriers, the supported iron-based catalyst prepared by the method of the present invention uses pure silicon molecular sieve as a carrier, and the weak interaction with the active center Fe can effectively inhibit the activity of the water gas shift reaction. When the CO conversion rate is above 80%, the yield of its byproduct CO2 is suppressed to below 10%. In addition, the addition of Mg and K additives effectively regulates the distribution of the product. The method of the present invention has a simple preparation process and is easy to operate, which can greatly reduce equipment investment and production operation costs.

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a low CO2 yield iron-based Fischer-Tropsch synthesis catalyst, characterized in that: include: 1) Preparing a pure silicon molecular sieve carrier; 2) Dissolving the precursors of metal Fe, Mg and K in water, impregnating the pure silicon molecular sieve carrier according to a metal iron loading of 20% to 40%, ultrasonically treating the obtained mixed solution, aging and drying to obtain a catalyst precursor; 3) calcining the catalyst precursor to obtain the low CO2 yield iron-based Fischer-Tropsch synthesis catalyst.

2. The preparation method according to claim 1, characterized in that: The pure silicon molecular sieve carrier includes one or more selected from the group consisting of acid-treated dealuminated Beta molecular sieve and hydrothermally synthesized pure silicon Beta molecular sieve, MCM-41 molecular sieve, SBA-15 molecular sieve, KIT-6 molecular sieve, and Silicalite-1 molecular sieve.

3. The preparation method according to claim 2, characterized in that: The reaction conditions of the acid-treatment dealumination include: a temperature of 80 to 120° C., a nitric acid concentration of 5 wt % to 65 wt %, and a stirring time of 12 h to 48 h.

4. The preparation method according to claim 1, characterized in that: In the step 2), the precursor of metal Fe is selected from one or more of ferric nitrate nonahydrate, anhydrous ferric chloride, and ferric citrate; the precursor of metal Mg is selected from one or more of anhydrous magnesium chloride, magnesium sulfate, and magnesium oxide; the precursor of metal K is selected from one or more of potassium chloride, potassium carbonate, and potassium nitrate.

5. The preparation method according to claim 1, characterized in that: In the step 2), the content of metal Mg and K in the precursor solution is doped according to the element molar ratio of Mg / Fe=0.05-0.5 and K / Fe=0.05-0.

2.

6. The preparation method according to claim 1, characterized in that: The drying temperature in step 2) is 80-120°C; And / or the calcination temperature in step 3) is 450-600°C.

7. The preparation method according to claim 6, characterized in that: The calcination temperature in step 3) is 550°C.

8. The preparation method according to claim 1, characterized in that: In the step 3), the calcination conditions are calcination at 450-600° C. for 3-5 hours, and a heating rate of 2° C. / min-10° C. / min.

9. A low CO2 yield iron-based Fischer-Tropsch synthesis catalyst, characterized in that: The low CO2 yield iron-based Fischer-Tropsch synthesis catalyst is prepared by the preparation method of the low CO2 yield iron-based Fischer-Tropsch synthesis catalyst according to any one of claims 1 to 8.

10. A Fischer-Tropsch synthesis method, comprising contacting a mixture of carbon monoxide and hydrogen with a catalyst under Fischer-Tropsch synthesis reaction conditions, characterized in that: The catalyst is the low CO2 yield iron-based Fischer-Tropsch synthesis catalyst as described in claim 9.